MORPHOLOGICAL VARIATION OF LONG-LEGGED VELVET MITE LARVAE IN DEEP TIME (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Parasitengona, an ingroup of Trombidiformes, is characterised by a complex life cycle, in which the larval stage is parasitic on animals. Larvae of erythraeoideans or long-legged velvet mites, one ingroup of Parasitengona, parasitise euarthropodan hosts and have extremely long legs that confer them the ability to walk fast. Representatives of Parasitengona in general, and Erythraeoidea in particular, are relatively abundant in the fossil record. Nonetheless, their studies have remained scarce, since, like in most mites, the characters needed for taxonomical identification are hidden within the amber piece. Here, we report 41 new erythraeoidean larvae from the Cretaceous Kachin amber and three specimens from Eocene Baltic amber. We also compare the shape of their habitus between extant and fossil specimens by applying elliptical Fourier analysis (EFA) to their redrawn outlines. According to the shape analysis, there is a certain level of overlap in the morphospace between extant and fossil specimens, but the difference in morphology was statistically significant, pointing to a separation between the two. This is supported by the fact that some morphological characteristics of fossil specimens are not present in extant representatives. Fossil erythraeoideans occupy the area of the morphospace with more elongated legs, which could be related to variations in the availability of their hosts or changes in microhabitat occupied by the mites, although bias in the fossil record cannot be ignored. Although preliminary, our findings demonstrate that quantitative morphological analysis can be applied to specimens of mites not preserved in the best of conditions that may not be of interest for taxonomic studies.
Keywords: Erythraeoidea; Baltic amber; Kachin amber; elliptic Fourier transformation.